Tingkat kemampuan literasi digital peserta didik kelas V SD se-Kecamatan Laweyan - Nafisah, Ainun; Atmojo, Idam Ragil Widianto; Ardiansyah, Roy (Jurnal Pendidikan Dasar, 2023)
The purpose of this study was to determine the level of digital literacy of fifth grade elementary school students in Laweyan District. The research method used is quantitative. The sample of this study was 86 students from 4 elementary schools in Laweyan District, class V. The data collection technique used is a test. Data analysis used descriptive statistical analysis. The results of this study are that the digital literacy level of fifth grade elementary school students in Laweyan District is mostly in the high category, which is 50%. Meanwhile students with very high category were 31.4%, low category were 1.2%, medium category were 17.4%. This research can be used as a reference to measure the level of digital literacy of students.